The value of feed lot lighting - Lipper, R.; Smith, E.F.; Richardson, D.; Boren, Fred W. (Kansas Agricultural Experiment Station, 2011)
In the two tests reported here the concentrate mixture or roughage-concentrate mixture was before the animals at all times. In addition a small amount of prairie hay was fed. In Lots 6 and 3 yearling Hereford feeder heifers was used, in Lots 17 and 13, yearling Hereford steers were the experimental animals. All the animals graded good to choice as feeders.
Keywords: Beef; Feedlot; Pen Lighting